A study on the feasibility of constructing an underground reservoir in Singapore with an integrated pumped-storage hydropower system (focusing on the water source) - Goh, Jen Loong (2017)
Since independence, the Singapore government have been actively searching for a sustainable water source. For a country with limited land and water resources, utilizing the available underground space to increase the water storage capacity seem viable, and practical. Hence, this report seeks to determine the feasibility of constructing an underground cavern within the competent rocks of the Bukit Timah Granite formation, where an underground hydropower system is incorporated to harvest the potential and kinetic energy from the falling water. This report delivers a conceptual design of a pumped-storage hydropower system designed for Singapore. The proposed facility will integrate an existing surface reservoir with the constructed caverns located 50m beneath. The constructed caverns will house the lower reservoir and a powerhouse, while the existing surface reservoir serve as the upper reservoir. In this study, the viability of the project shall be evaluated based on the following key aspects pertaining to constructing an underground pumped-storage hydropower facility in Singapore. The key aspects includes understanding the design considerations involved when constructing the proposed facility, identifying a suitable water source to meet the demands of the hydropower system, and discussing possible alternative output of water from the underground cavern. To evaluate the economic feasibility of integrating the said underground facility in Singapore, a simplified cost-benefit analysis for the operational phase is considered, where a minimal price differential between the sale and cost of power is identified to achieve breakeven. Whilst evaluating the feasibility of constructing the said underground facility based on the aforesaid aspects, both direct and indirect benefits which may arise due to the construction are presented. A key benefit will be the increased reliability of future water supply, where the dependency on imported water is reduced. Moreover, the concept of utilizing underground space will enable more surface land to be used more economically. By evaluating the aforesaid matters, this preliminary study presents the arguments which explains the feasibility of constructing the said underground facility within the competent rocks of Bukit Timah Granite formation for the purpose of increasing the water storage capacity; whereby the inclusion of a hydropower system will likely be operationally cost sustainable. Nevertheless, as the rock competency of Bukit Timah Granite formation is solely evaluated based on previous site investigation reports, further site investigation works will be required at the proposed sites to reaffirm the conclusion.